2014
DOI: 10.1590/s0004-28032014000400004
|View full text |Cite
|
Sign up to set email alerts
|

PERIANAL COMPLETE REMISSION WITH COMBINED THERAPY (SETON PLACEMENT AND ANTI-TNF AGENTS) IN Crohn’s DISEASE: a Brazilian multicenter observational study

Abstract: -Background -Perianal fistulizing Crohn's disease is one of the most severe phenotypes of inflammatory bowel diseases.Combined therapy with seton placement and anti-TNF therapy is the most common strategy for this condition. Objectives -The aim of this study was to analyze the rates of complete perianal remission after combined therapy for perianal fistulizing Crohn's disease. Methods -This was a retrospective observational study with perianal fistulizing Crohn's disease patients submitted to combined therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…The potential reasons for higher closure rates in our study could be explained by the early intervention with biologics after initial surgery (median time to initiation of anti‐TNFs only 6 weeks) and the removal of seton in a significant proportion of patients facilitating closure of the fistula tract. Our results are similar to a recent small Brazilian multicentre study using combined therapy of seton placement and anti‐TNFs agent which reported a complete perianal remission in 52% of patients . The highest fistula closure rates reported so far is from a single‐centre study from China, which reported 89.3% (25/28) clinical closure rates at week 30 using multimodality treatment .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The potential reasons for higher closure rates in our study could be explained by the early intervention with biologics after initial surgery (median time to initiation of anti‐TNFs only 6 weeks) and the removal of seton in a significant proportion of patients facilitating closure of the fistula tract. Our results are similar to a recent small Brazilian multicentre study using combined therapy of seton placement and anti‐TNFs agent which reported a complete perianal remission in 52% of patients . The highest fistula closure rates reported so far is from a single‐centre study from China, which reported 89.3% (25/28) clinical closure rates at week 30 using multimodality treatment .…”
Section: Discussionsupporting
confidence: 89%
“…Our results are similar to a recent small Brazilian multicentre study using combined therapy of seton placement and anti-TNFs agent which reported a complete perianal remission in 52% of patients. 23 The highest fistula closure rates reported so far is from a single-centre study from China, which reported 89.3% (25/28) clinical closure rates at week 30 using multimodality treatment. 24 In this study, preoperative MRI was used to guide drainage of all cavities by EUA followed by a rapid initiation of anti-TNF within 1 week after surgery followed by early removal of setons.…”
Section: Discussionmentioning
confidence: 97%
“…Also, four studies directly comparing (combined) anti‐TNF and seton drainage on closure and recurrence rates were analysed separately . Finally, 34 cohort studies and case‐series on anti‐TNF treatment were analysed .…”
Section: Resultsmentioning
confidence: 99%
“…After seton drainage, an aggressive top-down strategy was advocated instead of a step-up approach, supported by evidence that the early use of BIOs induces higher remission rates for anorectal complex fistulas associated with CD 15,24) . Ma et al 25) mentioned that the early initiation of IFX or ADA within the first 2 years of diagnosis reduces the rate of surgery and secondary loss of response, which requires dose escalation.…”
Section: Discussionmentioning
confidence: 99%